EXPERIMENTAL DETERMINATION OF LINEAR DYNAMIC MODEL PARAMETERS OF THE SEPARATELY EXCITED BRUSHED DC MOTOR BY MODIFIED PÁSEK’S METHOD (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper aims to propose a modified version of Pásek’s method for determining the linear dynamic model parameters of the separately excited brushed dc motor, i.e., equivalent electrical resistance and self-inductance of a rotor-armature electrical circuit, rotational mutual inductance, viscous friction torque coefficient and moment of inertia referred to the common rotational axis of the rotor, commutator, and motor shaft. The proposed method employs the transient response of rotor-armature electrical current to a sudden step increase in dc voltage at rotor-armature electrical circuit terminals of the motor, which is initially operating at steady-state no-load conditions.
Keywords: Separately excited brushed dc motor; Linear dynamic model parameters; Experimental determination; Modified Pásek’s method